Characterizing customer attrition mitigation strategies in container-based sanitation (CBS) organizations: the challenge of the public-private continuum - Ventura, Rebecca; VanRiper, Froggi; Javernick-Will, Amy (Frontiers in Environmental Science, 2024)
An estimated 3.6 billion people lack safely managed services globally, many of whom live in challenging urban contexts and face multiple barriers to accessing safely managed sanitation. These households need solutions that span the entire sanitation chain, from waste containment to waste treatment and disposal. Container-based sanitation (CBS) is one such solution. CBS organizations provide safely managed sanitation services to subscribers and largely depend on customers subscribing and remaining subscribed to their services. However, these organizations report that they experience high rates of customer attrition, which can make sustaining operations and/or meeting community sanitation goals difficult. Few studies have investigated the strategies being implemented to mitigate this attrition. To address this need, we used an exploratory case study approach, interviewing employees from seven CBS organizations and collecting organizational documentation, to identify the perceived drivers and strategies employed to mitigate attrition. The dominant perceived driver of attrition was economic challenges faced by subscribers, and the most common strategy to mitigate this attrition was developing individual repayment plans. Notably, organizations described attrition mitigation strategies that ranged along a public-private continuum. Strategies carried important tradeoffs, for example, private-leaning strategies often limited cases’ ability to service the most economically challenged households while reducing their risk to operational sustainability. Public-leaning strategies often sought to maximize the households serviced through external funding and subsidies; a long-term goal of some respondents. Future research should consider longitudinally studying CBS organizations to better understand their movement along the public-private continuum and how these essential sanitation services could be best supported by public actors.